THE HISTORY AND DEVELOPMENT OF THE SAINT LUCIA CIVIL CODE - Liverpool, N. (Revue générale de droit)

(untitled) (Éditions de l’Université d’Ottawa, 1983)
The Civil Code of St. Lucia was copied almost verbatim from the Québec Civil Code and promulgated in the island in 1879, with minor influences from the Civil Code of Louisiana.It has constantly marvelled both West Indians and visitors to the region alike, that of all the former British Caribbean territories which were subjected to the vicissitudes of the armed struggles in the region between the Metropolitan powers resulting infrequent changes is sovereignty from one power to the other, only St. Lucia, after seventy-six years of uninterrupted British rule since its last cession by the French, managed to introduce a Civil Code which in effect was in direct conflict in most respects with the laws obtaining in its parent country.This is an attempt to examine the forces which were constantly at work in order to achieve this end, and the resoluteness of their efforts.